Baseline susceptibility of different European lepidopteran and coleopteran pests to Bt proteins expressed in Bt maize: a systematic review. Issue 1 (December 2016) - Priesnitz, Kai; Vaasen, Anja; Gathmann, Achim
Abstract Background Lepidopteran and coleopteran species are the most important pests in maize. They can be controlled using genetically modified (GM) crops expressing insecticidalBacillus thuringiensis (Bt ) proteins. The long-term success of this technology demands a pest resistance management. Important information for the successful management of resistance is the baseline susceptibility of the different target pests to the differentBt proteins. The data on baseline susceptibility should enable risk assessors and managers to assess whether a GM maize produces aBt protein in a high-dose to specific target organisms and resistance has evolved during the commercial cultivation of this GM maize events. Methods Our systematic search followed an a priori protocol including the database platforms Web of Science, Scopus, CAB abstracts, Science Direct and JSTOR. We additionally conducted a Google scholar search. We collated all search results and screened all retrieved articles using predetermined inclusion criteria. We identified 30 studies, which fulfilled the criteria of including a relevantBt protein, a relevant species, an appropriate endpoint, and field-derived pest generations reared in the laboratory no longer than three generations. We then made a quality assessment to discover if the studies considered the dose response curves with confidence intervals, described the protein source, tested the protein concentration and the protein activity via positive controls, use more than ten larvae per concentration, more than two replications, and more than five protein concentrations. Since no quantitative synthesis was possible the synthesis of the results was done in a narrative form. Results Seventy percent of the studies fulfilled five or more criteria and 17% fulfilled four of the seven criteria. SixBt proteins were tested on one or more of the four speciesOstrinia nubilalis, Helicoverpa armigera, Sesamia nonagrioides, andDiabrotica virgifera virgifera . We extracted the baseline susceptibility for the given protein-species-combinations and the test method with theBt protein applied either on the surface of the diet or incorporated. Although, the data displays a high heterogeneity and are thus hard to compare, they give an overview of the baseline susceptibility of lepidopteran/coleopteran pests toBt proteins. Conclusion Our systematic review illustrates the heterogeneity of the data and indicates the necessity of standard protocols for testing susceptibility of insect pests, which provide comparable data. The cultivation ofBt crops, as with any other plant protection measure, is likely to result in resistance evolution in the target pests. Industry, policy makers, and research should combine knowledge to protect the benefits of this technology.